WORKSHOP PENGGUNAAN COUNTIF EXCEL UNTUK SISTEM PENDUKUNG KEPUTUSAN BAGI PENDIDIK SMK KOLESE TIARA BANGSA BATAM - Darmansah; Novri Adhiatma; Rika Harman; Amrizal (JPMTT (Jurnal Pengabdian Masyarakat Teknologi Terbarukan), 2025)
This community service aims to improve the understanding of SMK Kolese Tiara Bangsa educators in using the COUNTIF function in Microsoft Excel as a tool in decision support systems. COUNTIF is a Microsoft Excel function that can be used to count data based on certain criteria and can be used in various applications, such as academic performance evaluation and data-driven decision-making. This activity included training and mentoring educators on these functions. The results of this activity indicated that educators were more proficient in data processing and understanding the concept of decision support systems. According to training evaluations, educators gained more confidence in using Microsoft Excel to analyze academic and administrative data. Furthermore, the program taught educators the importance of accurate data processing for academic decision-making. By using it correctly, educators can evaluate their learning outcomes in a more structured and seamless manner. It is hoped that this program will be the first step in improving data literacy among vocational school educators